RED AND BLUE IDEOLOGY : A FANTASY-THEME ANALYSIS OF BARACK OBAMA'S POLITICAL DISCOURSE - Jarrell, Kelly Elizabeth (East Carolina University, 2011)
This thesis will examine the rhetorical style of Barack Obama throughout the 2008 presidential campaign and his contentious push for health care reform, in order to provide insight into Obama's post-inaugural political discourse. Drawing upon a variety of critical and rhetorical theories--e.g., fantasy-theme analysis (Borman, 1982), the narrative paradigm (Fisher, 1984), and Kenneth Burke's (1969) notion of identification--I argue that Barack Obama's rhetorical style changed drastically after he took office on January 20, 2009. This shift in rhetorical style is especially significant given the declining support for the president since he took office. A total of six speeches have been selected from both the 2008 presidential campaign and those delivered post-inauguration. Based upon an analysis of these speeches, I will argue that Obama employed a unique rhetorical vision throughout his campaign by combining two politically polarized myths to create a blended ideological frame that emphasized notions of bipartisanship. The reason Obama was able to portray such a convincing rhetorical vision that embodied two polarized ideologies is because of his blended racial heritage. Obama's own story of independent success alongside his intimate ties with a disenfranchised group of Americans allowed him recast the American Dream and set forth a unique rhetorical vision that resonated with constituents. This rhetorical vision embodied a moralistic frame predicated on specific values and principles. This analysis also revealed a distinct rhetorical shift in Obama's post-inaugural discourse with regards to his use of narrative elements. Obama's pre-inaugural narratives reveal clearly defined actors who are formed through common archetypal characterizations. Obama pits the narratives' protagonists and antagonists against one another by characterizing them as heroes and villains. The heroes and villains of these stories were ascribed specific character traits and motives, and this enabled Obama to present clear action themes of good versus evil. The specificity of these characters provided Obama's audience with central characters they could identify with. Obama's post-inaugural narratives fail to embrace archetypal character themes or concrete characterizations that expose a clear villain or hero within the drama. As a result, his speeches have lost their dramatic element. These characters were portrayed as vague, obscure figures that lacked basic character motivation and a guiding ideological principle. Instead, these narratives focused on the materialistic benefits of proposed policies and materialistic values as they relate to economic stability. These narratives provide evidence of a distinct shift from the moralistic frame that supported notions of collectivism to a materialistic frame that promotes notions of free enterprise and individual gain. Obama's tendency to cater to conservative constituents demonstrates a confounding ideological shift which depicts an entirely separate candidate from the confident, bi-partisan leader evident throughout the 2008 Presidential Campaign.
Keywords: Communication; Narratives; Political; Rhetoric; Discourse analysis--Political aspects--United States; Obama, Barack